Harmonizing PKL Program with Level II KKNI Through the Use of Electronic Journal (Journal of Vocational and Career Education, 2022)
The implementation of Field Work Practice (PKL) has experienced several problems, one of the problems is that students experience confusion when filling out existing activity journals. To overcome these problems, electronic journals for PKL in accordance with the level 2 Indonesian National Qualification Framework (KKNI) are proposed. This study aims to develop electronic journals that are in accordance with level 2 KKNI. The research method used is the ADDIE, which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. Based on the feasibility test, effectiveness test of the developed PKL electronic journal, and the responses given by media experts and material experts, the criteria for the responses were very feasible. From the practicality test, the criteria were very practical. From the effectiveness test in the experimental class, the criteria were quite effective and significantly used by students to improve the competence of graduates of the light vehicle engineering study program. The conclusion of this study is that electronic journals are effective in improving the graduate competence. The novelty of this research is that it is electronic based and refers to the level 2 KKNI.